2005
DOI: 10.1158/1078-0432.ccr-04-1829
|View full text |Cite
|
Sign up to set email alerts
|

Expression Levels of TEL, AML1, and the Fusion Products TEL-AML1 and AML1-TEL versus Drug Sensitivity and Clinical Outcome in t(12;21)-Positive Pediatric Acute Lymphoblastic Leukemia

Abstract: Purpose: t(12;21)(p13; q22), present in f25% of pediatric precursor B-ALL, is highly sensitivity to L-asparaginase and the prognosis depends on the intensity of the treatment protocol. This study analyzes the relationship between the mRNA expression of the genes and fusion products involved in t(12;21), in vitro sensitivity to prednisolone, vincristine, and L-asparaginase, and longterm clinical outcome in t(12;21)+ acute lymphoblastic leukemia (ALL) patients. Experimental Design: Long-term clinical outcome in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 36 publications
1
17
1
3
Order By: Relevance
“…These properties concur with similar earlier observations, which also demonstrated that, although both clones derive from the same source, some of their genetic features might, nevertheless, differ completely. 14,16,19 Taking into account that, even in cases without a deletion the nonrearranged ETV6 gene is generally not expressed, 43,44 it appears likely that ETV6 inactivation is a critical step in the pathogenesis of E/R-positive leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…These properties concur with similar earlier observations, which also demonstrated that, although both clones derive from the same source, some of their genetic features might, nevertheless, differ completely. 14,16,19 Taking into account that, even in cases without a deletion the nonrearranged ETV6 gene is generally not expressed, 43,44 it appears likely that ETV6 inactivation is a critical step in the pathogenesis of E/R-positive leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the clinical and biological features in ALL patients carrying the translocation t(12;21) leading to the TEL-AML1 gene fusion. [27][28][29][30][31][32][33][34][35][36][37][38] None of those studies reported a low Hb level to be associated with TEL-AML1. One study addressed this issue, but failed to demonstrate a correlation between Hb and TEL-AML1, probably due to the limited number of patients analyzed (11/51 patients TEL-AML1 + ).…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal translocations of multiple Ets family members are frequent in various cancer types, including FLI-1 (3,4), ERG (3,5), ETV1 (6), ETV4 (7), and FEV, in Ewing's sarcomas and TEL/ETV6 in different types of leukemia, fibrosarcoma, lymphoma, and myelodysplastic syndrome (8)(9)(10), indicating a critical role for Ets factors in tumorigenesis. Furthermore, deregulated activity of Ets factors is observed in many cancers and apparently contributes not only to tumorigenesis but also to tumor progression, outcome, angiogenesis, epithelial-to-mesenchymal transition (EMT), and metastasis (11).…”
Section: Introductionmentioning
confidence: 99%